Hunted - Stiefvater, Maggie, 1981- (New York : Scholastic Inc., 2014)
Four children have discovered that they have spirit animals, a rare bond between human and animal that has launched them on a quest to save their world. The team heads to the forests of Eura, where another Great Beast is hidden.
Kirkus Review, December 2013.
5.0
3-6
670L
Keywords: Human-animal relationships -- Juvenile fiction; Good and evil -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Human-animal relationships -- Fiction; Good and evil -- Fiction; Shapeshifting -- Fiction; Fantasy; Human-animal relationship -- Fiction; Good and evil -- Fiction; Fantasy fiction; Quests (Expeditions) -- Fiction; Fantasy fiction